Newcastle Disease Virus infection study on duck and chicken in Subang district - Aprizal Panus; S. Setiyaningsih; N.L.P.I. Mayasari (Indonesian Center for Animal Research and Development (ICARD), 2015)
The objectives of this research were to study Newcastle Disease Virus (NDV) infection in Subang area and to examine the diversity of the circulating NDV. Swabs of cloacal and oropharynx, and serum were sampled from total of 393 chickens and 149 ducks in backyard farms and live bird markets located in 10 subdistricts. Screening of NDV in pool of 5-7 samples by real-time Reverse-Transcription Polymerase Chain Reaction (rRT-PCR) matrix (M) showed 19/67 (28.3%) cloacal and 8/67 (11.9%) pharyngeal pools of chicken samples; 18/67 (26.9%) of the pools excreted virus via cloaca and oropharynx, while the duck pools of 8/30 (26.7%) shed virus from cloaca. Virus isolation attempted on individual sample from positive pools yielded 18 isolates which the majority of the isolates showed homogeneous antigenic character, only some of these showed variations up to 2 Log2 with Lasota and 4 Log2 with Komarov antisera. Majority of isolates had a higher affinity to Komarov indicating their propencity to virulent strains. Pathogenicity examination using elution test showed 3 isolates virus were grouped to mesogenic strains and 15 isolates to velogenic strain, in agreement with rRT-PCR fusion results. HI test on 408 sera showed that NDV antibody was detected in 48 (12%) birds with titres ranging from 1 to 8 Log2; only about 13% of vaccinated chickens demonstrated protective antibody titre (≥3 Log2). Newcastle disease is still endemic in Subang with relatively low antigenic variation among circulating strains.